Analysis of heterogeneity of fatigue properties of double-sided electron beam welded 140-mm thick TC4 titanium alloy joints. (January 2021) - Long, Jian; Zhang, Lin-Jie; Zhang, Liang-Liang; Ning, Jie; Zhuang, Ming-Xiang; Zhang, Jian-Xun; Na, Suck-Joo
Graphical abstract: Highlights: Low cycle fatigue performance of 140-mm Titanium alloy welded joint was evaluated. The overlap region of two weld seams was the weakest region of the entire joints. Fatigue failure in the second layer occurred at BM, but the others appeared at WM. Underlying reasons were discussed based on microstructure analysis by SEM and TEM. Abstract: The double-sided electron beam welding (EBW) technique has a prominent advantage that the maximum thickness of the processable plates increases to about twice as much as for single-sided welding. However, there is no in-depth analysis of fatigue properties of the double-sided electron beam welded thick joints with unequal weld penetrations on both sides, especially in the region where two weld seams overlap each other. This research studied low-cycle fatigue properties of the materials in different zones in the thickness direction of a double-sided electron beam welded joint of TC4 titanium alloys with thickness of 140 mm, in which the weld seam on the upper and lower surfaces are about 95 mm and 55 mm in depth respectively. Moreover, S-N curves of the materials in different zones in the thickness direction were obtained. The results showed that low-cycle fatigue properties of the materials in the overlap region (at about 90 mm from the upper surface) of the two weld seams in the double-sided electron beam welded joint were obviously inferior to those in the other zones. By utilizing a high-resolution scanning electron microscope (SEM), the materials in different zones in the thickness direction of the joint were observed. Based on this, it was found that there were more second-phase precipitates in the overlap of the two weld seams compared with the other zones. The microhardness of the overlap region of the two weld seams was found to be higher than those of base metal (BM) and the other zones of the weld seam. Mechanical properties near the overlap region of the two weld seams in the thickness direction of the joint presented most significant heterogeneity, which was one of the important reasons for the weakening of overall mechanical properties of the joint. The research results are of significance for the design and application of a welded structure of titanium alloys with a large thickness in the fields, such as aviation and ships.